Psychological happiness among workers and volunteers at the COVID-19 Vaccine Center in Taif Governorate - Alosaimi, Jaza Obeid; Al-Hussein, Asmaa Abdulaziz (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the existence of psychological happiness among workers and volunteers in the (COVID-19) Vaccine Centers in Taif, and measure its level. The sample consisted of 61 randomly selected workers and volunteers of both sexes, at COVID 19 Vaccine Centers to find if there is any statistical significance in the differences on psychological happiness in relation to gender and occupation. The study used a descriptive survey and a 24-item measure of psychological happiness prepared by researchers. This scale was applied to a sample of 122 randomly chosen employees and volunteers at five Covid Vaccine Centers Taif: King Faisal Hospital, Mental Health Hospital, Children’s Hospital and Al-Faisaliah. Results concluded that the level of psychological happiness among the workers and volunteers was high with an average response of 2.745 out of 3. It also showed no statistically significant differences at the level (α≥0.05) on the psychological happiness of workers and volunteers in relation to gender and occupation.